2021
DOI: 10.1097/qad.0000000000003017
|View full text |Cite
|
Sign up to set email alerts
|

Safety and antibody response to two-dose SARS-CoV-2 messenger RNA vaccination in persons with HIV

Abstract: This study of SARS-CoV-2 mRNA vaccination in 14 persons with HIV (PWH) demonstrated uniformly high anti-SARS-CoV-2 receptor binding domain (RBD) antibody titres after two doses, despite varied titres after a single dose. The majority of vaccine reactions were mild and no adverse events occurred.Conflicts of interest D.L.S. has the following financial disclosures: consulting and speaking honoraria from Sanofi, Novartis, CSL Behring, Jazz Pharmaceuticals, Veloxis, Mallinckrodt, Thermo Fisher Scientific. C.M.D. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
68
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 26 publications
11
68
3
Order By: Relevance
“…A previous national survey found that about 37.1% of PLWH are concerned that COVID-19 vaccination may have severe side effects [ 4 ]. Our study extended the existing literature by reporting AEs after COVID-19 vaccination among PLWH [ 5 7 ]. In our study, the AE rates were 22.8% after dose one (D1) of the inactivated COVID-19 vaccination and 10.2% after dose two, which was not higher than the AE rates of the original inactivated COVID-19 vaccine trials in general population [ 8 , 9 ].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…A previous national survey found that about 37.1% of PLWH are concerned that COVID-19 vaccination may have severe side effects [ 4 ]. Our study extended the existing literature by reporting AEs after COVID-19 vaccination among PLWH [ 5 7 ]. In our study, the AE rates were 22.8% after dose one (D1) of the inactivated COVID-19 vaccination and 10.2% after dose two, which was not higher than the AE rates of the original inactivated COVID-19 vaccine trials in general population [ 8 , 9 ].…”
mentioning
confidence: 60%
“…In our study, the AE rates were 22.8% after dose one (D1) of the inactivated COVID-19 vaccination and 10.2% after dose two, which was not higher than the AE rates of the original inactivated COVID-19 vaccine trials in general population [ 8 , 9 ]. The AE rates of inactivated COVID-19 vaccine in our study was lower than that of mRNA COVID-19 vaccine [ 5 , 6 , 10 ] and adenovirus vector COVID-19 vaccine [ 7 ]. We conclude the adverse events after the two-dose of inactivated COVID-19 vaccination among PLWH are minimal and mild.…”
mentioning
confidence: 68%
“…Five studies conducted in people living with HIV found low non-response rates ranging from 0 to 4% [ 48 , 68 , 179 ] (among those, two studies were estimated of good quality in the risk of bias assessment [ 48 , 68 ]) or comparable antibody titres compared to an HIV-negative population [ 41 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has suggested a lower magnitude humoral and cell-mediated immune responses [86][87][88] or shorter duration of the antibody response in comparison to the general population, 89 although both observations require further study. Recent studies suggest that the immune response following vaccination is equal amongst PLWH and the general population 90 and in comparison to those with other immunocompromising conditions, 91 but further work is needed to confirm these findings given the global concern for sustained immunity to SARS-CoV-2 and the known poorer responses to immunization for other infections among PLWH. [92][93][94][95][96][97] This includes suboptimal responses to vaccination to prevent against yellow fever, 93,94 , Hepatitis B, 96 , influenza, 95 polio, diphtheria, and tetanus.…”
Section: Immunity In Immunocompromised Individualsmentioning
confidence: 99%